Community forestry in Nepal - Paudel, S. (Himalayan Journal of Sciences, 2006)
Establishment of community forestry in Nepal is a successful step in conservation of forest. Community forestry programme through the local forest users group has shown its positive impacts in the society. This paper discusses an overview of the present scenario of the community forestry in Nepal. It describes the brief historical background, some important forest legislations, and organization of forest. The paper also describes the internal conflicts between forest users and district forest offices, and possible resolution. It also suggests some of the aspects of community forestry in which the research needs to be focused for the better management of the forests in Nepal.Himalayan Journal of Sciences 1(1): 62-65, 2003